Navigating Suicidal Crisis in a Traditional Setting of Kyrgyzstan - Salimova, Leila (Asean Social Work Journal, 2024)
The Case Study of Azat (name is changed) represents a joint effort of data gathering from the Researcher, the Social Pedagogue and other community members from one of the remote local schools in Kyrgyzstan. By using phenomenological research methods including non-structured interviews (n=3), observations and field trips, the researcher strived to understand and describe the essence of the phenomenon of suicide in a conservative country, like Kyrgyzstan. The study highlights the challenging circumstances faced by Azat, a 14-year-old residing in a village in Kyrgyzstan. Azat's family grapples with financial instability, parent’s labor migration, and sibling abuse, all of which have led to distressing experiences for him, including two suicide attempts. The analysis emphasizes the significance of understanding ecological systems and societal constructs in social work practice. It underscores the vital role of social workers in advocating for marginalized individuals like Azat, with suggested interventions including psychological support, collaboration with school professionals, and ongoing family visits to monitor progress and provide assistance. This case exemplifies the critical need for holistic, empathetic, and culturally sensitive social work interventions in addressing complex psychosocial challenges within vulnerable families.